Synthesis of anthraquinone derivative (DHAQC) and its effect on induction of G2/M arrest and apoptosis in breast cancer MCF-7 cell lines - Yeap, Swee Keong; Akhtar, Muhammad Nadeem; Kian, Lam Lim; Abu, Nadiah; Wan, Yong Ho; Zareen, Seema; Roohani, Kiarash; Huynh, Ky; Sheau, Wei Tan; Lajis, Md. Nordin; Mohamed Alitheen, Noorjahan Banu (Dove Medical Press, 2015)
Anthraquinones are an important class of naturally occurring biologically active compounds. In this study, anthraquinone derivative 1,3-dihydroxy-9,10-anthraquinone-2- carboxylic acid (DHAQC) (2) was synthesized with 32% yield through the Friedel-Crafts condensation reaction. The mechanisms of cytotoxicity of DHAQC (2) in human breast cancer MCF-7 cells were further investigated. Results from the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that DHAQC (2) exhibited potential cytotoxicity and selectivity in the MCF-7 cell line, comparable with the naturally occurring anthraquinone damnacanthal. DHAQC (2) showed a slightly higher IC50 (inhibitory concentration with 50% cell viability) value in the MCF-7 cell line compared to damnacanthal, but it is more selective in terms of the ratio of IC50 on MCF-7 cells and normal MCF-10A cells. (selective index for DHAQC (2) was 2.3 and 1.7 for damnacanthal). The flow cytometry cell cycle analysis on the MCF-7 cell line treated with the IC50 dose of DHAQC (2) for 48 hours showed that DHAQC (2) arrested MCF-7 cell line at the G2/M phase in association with an inhibited expression of PLK1 genes. Western blot analysis also indicated that the DHAQC (2) increased BAX, p53, and cytochrome c levels in MCF-7 cells, which subsequently activated apoptosis as observed in annexin V/propidium iodide and cell cycle analyses. These results indicate that DHAQC (2) is a synthetic, cytotoxic, and selective anthraquinone, which is less toxic than the natural product damnacanthal, and which demonstrates potential in the induction of apoptosis in the breast cancer MCF-7 cell line.